PROGRAM BIMBINGAN DAN KONSELING KEMATANGAN KARIR SANTRI SMA PONDOK PESANTREN - Muntolib; Alim, Akhmad; Rahman, Imas Kania (Universitas Islam Negeri Alauddin Makassar, 2023)
This research is motivated by the fact that senior high school students at Islamic boarding schools have problems in career maturity, namely not being able to prepare and plan a career properly. This causes a loss of time, finance, and learning failure for these students. This research is a type of qualitative research with a case study approach that aims to explore the career maturity program of Islamic boarding school students through primary and secondary literature related to the research object and then integrated with field research in an effort to create a career maturity guidance and counseling program for Islamic boarding school students. This research resulted in a career maturity guidance and counseling program for high school Islamic boarding school students in accordance with the Minister of Education and Culture Number 111 of 2014 and the Operational Guidelines for the Implementation of High School Guidance and Counseling (SMA) of the Ministry of Education and Culture Directorate General of Teachers and Education Personnel 2016 which has the following structure : 1) rationale, 2) legal basis, 3) vision and mission, 4) description of needs, 5) objectives, 6) program components, 7) service areas, 8) operational plan (action plan), 9) theme/topic development , 10) evaluation plan, reporting and follow-up, 11) infrastructure and budget.